SPATIAL DISTRIBUTION OF BRACKISHWATER POND SOIL CHARACTERISTICS IN PEKALONGAN CITY CENTRAL JAVA PROVINCE - Andi Indrajaya Asaad; Akhmad Mustafa (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
Spatial distribution of brackishwater pond soil has a vital role in the system of bioenvironment including brackishwater pond environment. This research was aimed to determine the spatial distribution of brackishwater pond soil characteristics in Pekalongan City, Central Java Province. A total of 59 sampling points each with two different soil depth samplings were determined by simple random method. A total of 21 soil characteristics were measured in the field and analyzed further in the laboratory. Geostatistic with Kriging Interpolation method in the ArcGIS 9.3 software were used to depict the distribution of the data across the landscape. Furthermore, the spatial distribution was presented by using ALOS AVNIR-2 image. Research result indicates that in general, pond soil in Pekalongan City can be classified as soil with high variability or relatively heterogenic with the value of variation coefficient more than 36%. Soil characteristics which have similar pattern of spatial distribution are acid sulfate soil and soil nutrient content. High value of pH, organic matter, and total-N of soil, and on the other hand, low value of PO4 were generally found in the pond area of Krapyak Lor Village, while in Pekalongan City, it was found high clayish soil content but relatively homogenous. It is recommended that pond management must be based on soil characteristics which are different from one area to another. The soil characteristics itself can be drawn and assessed through spatial distribution.